Antibiotic Sensitivity of Escherichia Coli Museum Strains After Long-Term Storage in a Lyophilized State at Moderately Low Temperatures - Yagnuk , Yulia; Gurina, Tetiana; Peretyatko, Olena; Sklyar, Nadia; Yagnuk , Аndrii; Kalinichenko, Svitlana (Problems of Cryobiology and Cryomedicine, 2023)
Sensitivity of microbial cultures to antibiotics was determined using the disco-diffusion method, broth serial dilution and agar serial dilution. Restored viability and detection of antibiotic resistance in the museum Escherichia coli strains stored for a lasting time in a lyophilized state indicates that freeze-drying in combination with moderately low temperatures for subsequent long-term storage is an effective method of maintaining a collection of microorganism strains in a functionally stable state, including preservation of their antibiotic resistance. It was found that one of the 21 studied strains was resistant to ampicillin, ampicillin-sulbactam, cephalosporins of the I–III generations, two strains were resistant to chloramphenicol, and four strains were insensitive to tetracycline. Detection of the resistance to cephalosporins and protected penicillins in E. coli strain isolated in 1963, long before the discovery and use of these antibiotics in clinical practice, confirms that antibiotic resistance is a phenomenon associated rather with the general mechanisms of adaptation of pathogens to adverse external environmental factors than with the widespread use of antimicrobial drugs. Probl Cryobiol Cryomed 2023; 33(2):115–121